THE CORRELATION BETWEEN LITHIUM AND MAGNESIUM IN TRIOCTAHEDRAL MICAS: IMPROVED EQUATIONS FOR LI2O ESTIMATION FROM MGO DATA - Tischendorf G.; Förster H.J.; Gottesmann B. (My University, 1999)
A major disadvantage of the electron microprobe is its inability to determine Li, which may make up an essential component in micaceous minerals. Correct classification of micas and proper calculation of their formulae require alternative methods. One of these is the indirect estimation of the lithium concentration by empirical approaches based on element correlations. Relationships between Li 2 O and SiO 2 have long been used for this purpose; however, they are valid only for a limited range of mica compositions (i.e. Li-rich, Mg-poor varieties). In this paper we report the results from a renewed study of the correlation between Li 2 O and MgO contents in trioctahedral micas. It is demonstrated that the relations between both oxides are strongly dependent upon the geological environment in which the mica was formed. It is necessary to distinguish a ‘normal group’, which comprises micas from ‘common’ S- and I-type magmatic rocks and most metamorphic rocks , a ‘low Li-Mg group’, to which belong Fe-rich micas from non-alkaline rocks of A-type affinity, and a ‘high Li-Mg group’ which includes micas from either peraluminous or peralkaline igneous rocks and Mg-enriched wall-rocks. These wall rocks supplied additional magnesium to the mica-forming environment. We offer empirical expressions relating Li 2 O and MgO contents for these three types which, in many cases, allow a sufficiently good estimation of the lithium content in trioctahedral micas of widely varying compositions.